Pelayanan Proses Penerbitan Kartu Tanda Penduduk Berbasis Elektronik (KTP-el) - Desilia Purnama Dewi; Harjoyo Harjoyo; Rudi Irawan (Universitas Musamus, Merauke, Papua, 2020)
Civil administration of services that goes on the Departement of Population and Civil Registration, inKarawang Regency's are experiencing delays in the issuance of KTP-el, many citizen who have carryKTP-el recording in their respective Districts, in reality there are still many residents who have notreceived KTP-el because the issuance exceeds the time set. The aims of this research is to understandcomprehension how the service inside process of issuing KTP-el and specifically to find out the servicein the process of issuing KTP-el at the Department of Population and Civil Registration Karawang andthe solution to people who have multiple data. This type of study is descriptive research using a qualitativethrough case study methods. Data collection methods have the shape choise of in-depth interviewsthrough key informant's, immediate observation of the practice of services and documentation proceeds.The analysis technique uses data source triangulation. Based on the discussion and results regardingServices in the Process of Issuance of KTP-el can be states that the stages of KTP recording serviceshave been registered and running well through in the population database using the application of SIAK,the problem that occurs is the limited KTP-el blanks that have an impact on delays in the process ofissuing KTP-el which should be resolved within fourteen working days and the implementation of lifelongKTP-el with the concept of the One Day Service Catpil as a medium for submitting data unification andsubmitting new KTP-el issuance.